Cryptographic service optimization scheduling algorithm for collaborative jobs in cloud environment - CAO Xiaogang; LI Fenghua; GENG Kui; LI Zifu; KOU Wenlong (Tongxin xuebao)
In response to the demand for collaborative computation of multi-cryptographic jobs in cryptographic on-demand services within a cloud environment, a multi-cryptographic job collaborative scheduling algorithm was proposed. This algorithm effectively addressed new challenges in cloud environments, such as a variety of cryptographic algorithm types, high concurrency demands, random cross-job interactions, and sudden increases in workloads. Considering the dependencies among jobs, makespan of jobs and computational power of computing units, the scheduling problem for multi-cryptographic job collaborative service was modeled as a multi-objective optimization workflow scheduling problem. A two-stage “select-sort” scheduling algorithm was proposed. In the selection stage, the improved NSGA-III algorithm was employed to select computing units for cryptographic computing jobs, and in the sorting stage, the execution order was determined based on the urgency of jobs. Simulation results demonstrate that the proposed algorithm outperforms traditional scheduling algorithms in terms of energy consumption, migration costs, and adaptability to transient surges in loads.